Energy Cost of Selected Physical Activities of Older Persons Living in Taguig City, the Philippines - Lat, Hazel T.; Lim, Chelcey Lauren T.; Velasquez, Magnolia B.; Mendoza, David Kenneth C.; Tan, Robby Carlo (2024)
The promotion of physical activity is important for fostering healthy aging. However, a
substantial proportion of older adults remain sedentary. Current metrics assessing the energy cost of physical activity are primarily designed for the general adult population and inadequately account for distinct physiological changes in older individuals – encompassing variations in muscle mass, bone density, metabolism, and overall functional capacity. This study aimed to determine the energy cost of selected physical activities of Filipino older persons. This crosssectional study conducted in Taguig City involved 19 older adults aged 60–79 yr using the COSMED Fitmate indirect calorimeter for resting metabolic rate determination, as well as the portable COSMED K5 indirect calorimeter for measuring energy cost of different physical activities – including treadmill walking, self-paced walking, a routine based on the DOST-FNRI manual, and multi-gym equipment. The outcomes of the study were presented in percentages and averages. Participants in the study were categorized based on their muscle strength and mass. Analysis revealed a consistent trend where older adults with lower appendicular skeletal muscle mass index and handgrip strength values demonstrated lower metabolic equivalent values across the different exercise routines. Notably, Routine 2 displayed an exception, with individuals above the 50th percentile of ASMI and HGS exhibiting lower METs than those below the 50th percentile. This study contributes insights into the energy cost of specific activities among older adults emphasizing the importance of physical activity in healthy aging and providing valuable information for tailored interventions and a nuanced understanding of energy expenditure in this age group.
Keywords: Excercise; Aging; Physical activity